Récurrences & Variations. - Lorent, Claude (Namur : Service de la Culture Namur, 2008)
Becher, Bernd & Hilla ; Copenaut, Martine ; Duhem, Paul ; Horn, Roni ; Zhuang Hui ; Kawara, On ; Lambotte, André ; McCollum, Allan ; Nixon, Nicholas ; Opalka, Roman ; Raynaud, Jean Pierre ; Tharin, Emmanuel ; Toroni, Niele ; Warhol, Andy
biog. + kleine tekst per kunstenaar p. 41-54
Frans
Exhibition. Récurrences & Variations. Maison de la Culture Namur, 10.05.2008 - 29.06.2008.
boek